AV3V LESION REDUCES THE PRESSOR, DIPSOGENIC, AND NATRIURETIC RESPONSES TO VENTROMEDIAL HYPOTHALAMUS ACTIVATION - Valladao, A. S.; Saad, W. A.; Camargo, LAD; Renzi, Antonio [UNESP]; Deluca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1992)
In the present study, we investigated the effect of anteroventral third ventricle (AV3V) lesion on pressor, tachycardic, dipsogenic, natriuretic, and kaliuretic responses induced by the injection of the cholinergic agonist carbachol into the ventromedial hypothalamic nucleus (VMH) of rats. Male rats with sham or AV3V lesion and a stainless steel cannula implanted into the VMH were used. Carbachol (2 nmol) injected into the VMH of sham rats produced pressor (32 +/- 4 mmHg). tachycardic (83 +/- 14 bpm), dipsogenic (8.2 +/- 1.1 ml/h). natriuretic (320 +/- 46-mu-Eq/120 min), and kaliuretic (155 +/- 20-mu-Eq/120 min) responses. In AV3V-lesioned rats (2 and 15 days), the pressor (4 +/- 2 and 15 +/- 2 mmHg. respectively), dipsogenic (0.3 +/-0.2 and 1.4 +/- 0.7 ml/h), natriuretic (17 +/- 7 and 99 +/- 21-mu-Eq/120 min), and kaliuretic (76 +/- 14 and 79 +/- 7-mu-Eq/120 min) responses induced by carbachol injection into the VMH were reduced. The tachycardia was also abolished (27 +/- 15 and -23 +/-29 bpm, respectively). These results show that the AV3V region is essential for the pressor, tachycardic, dipsogenic, natriuretic. and kaliuretic responses induced hy cholinergic activation of the VMH in rats.
Keywords: ARTERIAL PRESSURE; WATER INTAKE; FLUID BALANCE; ELECTROLYTE BALANCE; AV3V REGION